Original paperEvaluation of prophylaxis using low doses of heparin associated with aspirin in pregnancy with multiple miscarriages and high antiphospholipid antibody levels - preliminary report - Spegiorin, Ligia Cosentino Junqueira Franco; de Godoy, José Maria Pereira; Orliani, Antonio Helio (Archives of Medical Science, 2007)
Introduction: Gestation constitutes a state of acquired hypercoagulability and the success of a pregnancy depends on an adequate placental blood circulation. The objective of this study was to evaluate the evolution of pregnant women suffering from antiphospholipid antibody syndrome and repetitive miscarriages treated with low doses of heparin and aspirin. Material and methods: The patient report cards of 27 patients with histories of multiple miscarriages (2 or more events) and who suffered from antiphospholipid antibody syndrome were reviewed over 32 gestations. The ages of the gravidas were between 17 and 41 years old with a mean age of 26.6 years. Inclusion criteria included positive tests for lupus anticoagulant and anticardiolipin antibodies. The use of subcutaneous heparin at 5000 IU was recommended twice daily in these cases, as was the oral administration of 100 mg of aspirin. Results: Of the 32 gestations studied 84.4% were successful and 15.6% miscarried. Gestational ages at delivery varied from 34 to 41 weeks, with a mean of 37 weeks. Gestational ages for the foetal losses varied from 7 to 26 weeks with an average of 15.2 weeks. Conclusions: The association of heparin at the recommended dosage with aspirin was efficient in preventing miscarriages in patients with histories of repetitive foetal loss.